Questions of character : illuminating the heart of leadership through literature - Badaracco, Joseph, Jr. (Boston, Mass. : Harvard Business School Press, 2006)
"Joseph Badaracco argues that literature helps leaders develop personal answers to specific questions. Serious fiction provides fresh, powerful perspectives on the fundamental dilemmas facing today's managers and executives. While reading compelling stories in which memorable protagonists grapple with questions of character, leaders can watch them worry, hope, commit, exult, regret, and reflect, while being tested, strengthened, or weakened. These experiences deepen leaders' self-knowledge, enabling them to be more effective." "Badaracco examines eight universal leadership challenges through the lenses of celebrated stories."--Jacket.
Do I have a good dream? : Death of a salesman by Arthur Miller -- How flexible is my moral code? : Things fall apart by Chinua Achebe -- Are my role models unsettling? : "Blessed Assurance" by Allen Gurganus -- Do I really care? : The love of the last tycoon by F. Scott Fitzgerald -- Am I ready to take responsibility? : "The secret sharer" by Joseph Conrad -- Can I resist the flow of success? : I come as a thief by Louis Auchincloss -- How well do I combine principles and pragmatism? : A man for all seasons by Robert Bolt -- What is sound reflection? : Antigone by Sophocles -- Judging character.
Includes bibliographical references (pages 207-210) and index.
Keywords: Leadership; Leadership -- Moral and ethical aspects